Design and Optimization of Cationic Nanocapsules for Topical Delivery of Tretinoin: Application of the Box-Behnken Design, In Vitro Evaluation, and Ex Vivo Skin Deposition Study. (12th December 2021) - Ebrahimi, Saeed; Mahjub, Reza; Haddadi, Rasool; Vafaei, Seyed Yaser
Abstract : Cationic nanocapsules represent a promising approach for topical delivery purposes. We elaborated on a novel formulation based on the cationic nanocapsules to enhance the pharmacodynamic efficacy, user compliance, and photostability of tretinoin (TTN). To achieve this goal, TTN nanocapsules were prepared by the nanoprecipitation method. In order to statistically optimize formulation variables, a Box-Behnken design, using Design-Expert software, was employed. Three independent variables were evaluated: total weight of the cationic acrylic polymer (X 1 ), oil volume (X 2 ), and TTN amount (X 3 ). The particle size and encapsulation efficiency percent (EE%) were selected as dependent variables. The optimal formulation demonstrated spherical morphology under scanning electron microscopy (SEM), optimum particle size of 116.3 nm, and high EE% of 83.2%. TTN-loaded nanocapsules improved photostability compared to its methanolic solution. The in vitro release study data showed that tretinoin was released in a sustained manner compared to the free drug. The ex vivo skin permeation study demonstrated that greater drug deposition into the epidermal region rather than the deep skin was observed with a gel containing TTN-loaded nanocapsules than that of drug solution, respectively. The skin irritation test revealed that the nanoencapsulation of the drug decreased its irritancy compared to the free drug. These results revealed the promising potential of cationic nanocapsules for topical delivery of tretinoin